PENGEMBANGAN AGRIBlSNIS MELALUI MANAJEMEN TEKNOLOGI - Imam Hidayat, Syarif (MAPETA, 2002)
Agribusiness development is not new issue, many experts have discussed for it so much. Then some policies of Government have been created to develop agribusiness system. In reality the efforts have not yet reached objective the society agribusiness of Indonesia. In order to improve agribusiness condition, there are some ideas, for example the use of technology. As a method to enhance better life of people (the definition of technology) the technology beside can some benefits, so it will have the negative effects to business, system or environment where man usually live. Than technology management will be needed to make maximize benefit and to minimize risk. Key Words: Agribusiness development. Techno/ogy management